Secondary traumatic stress, level of exposure,empathy and social support in trauma workers - Macritchie, Victoria (My University, 2007)
A review of trauma literature indicated that in comparison to PTSD there is very little research into the effects of secondary trauma, especially with regards to trauma workers. The present study explored the psychological impact of trauma workers who work with victims of violent crimes. Both Figley’s (1995) trauma transmission model and Dutton and Rubenstein (1995) ecological model were used to develop a refined trauma model for trauma workers in South Africa, which formed the theoretical basis for the current research. This model looked at the relationships between specific key variables (level of exposure to traumatic material, empathy, and level of perceived social support) and secondary traumatic stress, and their interrelationship. In the present study relevant information was gathered from volunteer trauma workers (N=64) using self-report measures. Data was analysed using the following statistical techniques: Descriptive statistics, Pearson’s Correlation Coefficients, Two Independent Sample T-Test, and a Moderated Multiple Regression. Results indicated that the trauma workers, to some extent, experienced symptoms of secondary traumatic stress. In addition, it was found that previous exposure to traumatic material, level of empathy, and level of perceived social support have a significant relationship with secondary traumatic stress. Social support was not found to have a moderating effect, but empathy emerged as a consistent moderator between the trauma workers previous exposure to traumatic material and secondary traumatic stress. Results also revealed that ones qualification made no difference in the development of secondary traumatic stress. In summary, this study expanded on knowledge into the effects of criminal violence in South Africa, particularly with concern to trauma workers, a population often ignored. This study was considered to be a contribution to trauma literature as it provides much needed empirical evidence.
Student Number : 0102295F - MA research dissertation - School of Psychology - Faculty of Arts
Keywords: secondary traumatic stress; empathy; social support; level of exposure